'Living Artistically' under Post-Fordist Conditions. Issue 4 (2nd September 2020) - Matejić, Bojana
Abstract: ' Shaping one's life artistically' implies the principle 'I live as an artist when all my actions, and my expression in general, in connection with any content whatever, remain for me a mere show and assume a shape which is wholly within my power' (Hegel). Drawing on Hegel, the 'young' Marx advocated ' production in accordance with the laws of Beauty' ('artistic work/life'), as a kind of work which, inasmuch as it was 'free', provided a model for the elucidation of the presupposition of human emancipation. 'True Art' appears to be work performed under the umbrella of a 'free community', where the division between masters and slaves, working class and capitalists, emancipators and emancipated, is abolished. Does the conception of 'living artistically' (still) have a critical emancipatory value, and how can it be formulated under the conditions of a global market economy and post-Fordism, where every critical act, event and activity is appropriated?